Effect size assessment in quasi-experimental studies - O. V. Krasko (Informatika)
Objectives. To estimate effect sizes in quasi-experimental studies.Methods. Methods of the theory of estimation, methods of mathematical statistics.Results. Estimation of the effect size on an ordinal scale, estimation of the effect size on a binary in the case of opposite direction effects in groups, in quasi-experimental studies for the analytical method "differences in  differences".Conclusion. The paper considers approaches to assessing absolute and standardized effect sizes in experimental and quasi-experimental studies. A brief review of the estimators of absolute and standardized effect sizes for quantitative and binary study variables is provided. The applied approach is proposed to assess the effect sizes of a binary variable in the case of opposite direction effects in groups within a quasi-experimental studies for the "differences in differences" analytical method. An example of assessment of absolute and standardized effect sizes of quantitative and binary variables in quasi-experimental studies in clinical epidemiology is considered.